Validation of the Work Family Conflict Scale for Sexual Minority Employees. (November 2019) - Kim, Shin Ye; Velez, Brandon; Daheim, Jacob; Lei, Nina
The present study examined the factor structure, reliability, and validity of the Work–Family Conflict Scale (WFCS) in a sample of 295 sexual minority employees. Factor analyses supported a two-factor oblique model, with work–family conflict manifesting as worker role interfering with the family role (WIF) and family role interfering with the worker role (FIW). We also examined the relations of the latent WIF and FIW factors with conceptually related constructs. Both WIF and FIW were significantly negatively correlated with partner support; lesbian, gay, bisexual, and transgender–supportive climates; job satisfaction; and life satisfaction and were significantly positively correlated with turnover intentions, anxiety, and depression. Moreover, WIF (but not FIW) was significantly negatively associated with family support and family satisfaction, whereas FIW (but not WIF) was significantly negatively associated with outness at work. The findings of the present study suggest that the WFCS—and, possibly, the construct of work–family conflict more generally—holds promise for future vocational research focused on the interface of work and family in the lives of sexual minority employees. Implications of these findings for clinical work and research with sexual minority employees are discussed.